Developing Capacity to Integrate IT into Higher Education Teaching and Learning : Final Report for a 1997 Staff Development Grant. - Marshall, Stephen; Litchfield, Andrew (Committee for University Teaching and Staff Development, 2000)
This is a final report for a 1997 Staff Development Grant funded by the Committee for University Teaching and Staff Development. The report details the objectives and outcomes of a project that involved developing capacity to integrate IT into higher education teaching and learning. The report provides justification and educational rationale for the project development.